(untitled) (Asian Journal of Social Science Studies, 2022)
Recently, the Hubei face recognition case has aroused widespread concern in the society, and the protection of the basic rights of vulnerable groups in the Digital Divide has once again become a concern of the theoretical and practical circles. The Digital Divide is a phenomenon of social differentiation caused by the development of digital technology to a certain stage. The elderly and other vulnerable groups are limited by their own learning ability and adaptability, and have not been able to integrate into the smart society in time, and the government and enterprises have not paid enough attention to this kind of the additional difficulty of the disadvantaged groups in exercising their rights, so that social contradictions are gradually revealed. Establishing a reasonable social resource allocation mechanism and re-examining the law enforcement process of government departments will play an important role in protecting the basic rights of vulnerable groups in the Digital Divide.